2022
DOI: 10.3390/cancers14030577
|View full text |Cite
|
Sign up to set email alerts
|

Metformin as a Potential Treatment Option for Endometriosis

Abstract: Endometriosis is a common disease in women of reproductive age, and its pathogenesis seems to be largely affected by hormone imbalance, inflammation, oxidative stress, and autophagy dysregulation. These pathophysiological disturbances interact with one another through mechanisms that are still awaiting elucidation. The aim of this article is to present current knowledge regarding the possibilities of using metformin in the pharmacological treatment of endometriosis. Metformin is an insulin sensitizer widely us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 165 publications
0
12
0
Order By: Relevance
“…In addition, there are few plaque-stabilizing drugs targeting MMP-9. Metformin interferes with the pathophysiology of multiple cancers and diabetes by reducing MMP-9 expression [ 31 , 32 , 33 ]. However, there are still many studies showing that metformin can increase MMP-9 expression [ 34 ], including some clinical trials [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are few plaque-stabilizing drugs targeting MMP-9. Metformin interferes with the pathophysiology of multiple cancers and diabetes by reducing MMP-9 expression [ 31 , 32 , 33 ]. However, there are still many studies showing that metformin can increase MMP-9 expression [ 34 ], including some clinical trials [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, metformin administration in STZ-diabetic rats resulted in improved testosterone, LH and FSH hormones levels (Nasrolahi et al 2013 ). Various studies have shown that treatment with metformin is effective in reproductive system diseases, including female and male reproduction in endocrine pathologies (Lee et al 2019 ; Shpakov 2021 , ul haq Shah, Shrivastava et al 2022 ), endometriosis (Zhao et al 2018 , Mu et al 2020 , Stochino-Loi et al 2021 , Kimber-Trojnar et al 2022 ), polycystic ovary syndrome (Chen et al 2019 ; Fornes et al 2022 , Xu et al 2022 ) and prostate (Sun et al 2018 , Chen, Wang et al 2021a , b , c , Aydın et al 2022 , Morale et al 2022 ).…”
Section: Metformin and Therapeutic Goalsmentioning
confidence: 99%
“…Unfortunately, despite following the recommendations discussed above, as much as 15–30% of patients with GDM will require pharmacotherapy. The treatment of hyperglycemia in patients with GDM includes insulin, as well as oral medications, including metformin and glyburide [ 10 , 21 , 22 , 23 , 24 ]. Due to its structure, insulin is considered a safer drug than metformin and glyburide [ 25 ].…”
Section: Management Of Gdmmentioning
confidence: 99%